De alleronaangenaamste arbeid uit welke de ziel weinig voedzel trekt: de Præfatio van Mr. Hendrik Constantijn Cras tot zijn Catalogus Bibliothecæ Publicæ Amstelædamensis (1796) - Cras, Henrik Constantijn 1739-1820; Heesakkers, Chris L.; Visser, Piet 1949- (Amsterdam Vossiuspers, 2000)
Hendrik Constantijn Cras, renowned professor of law, was appointed librarian of the Athenaeum Illustre in 1785. This library was in deplorable condition at the time, and Cras was given the task of continuing the restoration work of his suddenly deceased predecessor Verheyk. Verheyk had already ensured that the building was restored, had the chains removed from the books and had new bookcases manufactured, with bars against thieves. Cras then arranged and described the library's book holdings with the help of booksellers Petrus den Hengst and Wedelmeyer.In doing so, he took an innovative approach. For instance, he was the first to decide to give the main titles of serial works a spine number, instead of the partial titles. He placed the books in alphabetical order within the usual subject division and then divided them into three sections according to format. He also did away with books in open display. A lending desk was introduced.In order to convince the city council of Amsterdam of the need to open up more to the public and to increase the number of books in the future, Cras had his Catalogus Bibliotheca preceded by an extensive preface with a sketch of the history of the library since the fifteenth century.
Keywords: 18th Century (1701-1800); Library; Philosophy; Amsterdam (Netherlands)